The role of redox homeostasis biomarkers in clear cell renal cell carcinoma development and progression - Mihailović, Smiljana (Medicinski podmladak, 2023)
The clear cell renal cell carcinoma (ccRCC) is the most frequent and the most aggresive subtype of renal cell carcinoma usually detected at an already advanced stage. It might even be observed as a metabolic disease since complex molecular changes and disturbed redox homeostasis are its hallmark. As certain changes are characteristic for tumorigenesis while some other for metastatic disease, the identification of metabolic modifications could also point out the stage of tumor progression. Hypoxia inducible factor, as a factor regulating transcription of genes encoding glycolytic enzymes, as well as controlling lipid accumulation, has a particular place in ccRCC development. Additionaly, disturbed redox homeostasis induces the Keap1/Nrf2 pathway which further modulates the synthesis of phase-II detoxifying metabolism enzymes. The upregulation of glutathione transferases, Pi class especially, inhibits kinase-dependent apoptosis that is essential in tumor progression. Furthermore, hydrogen peroxide (H2O2) acts as a signaling molecule conveying redox signals, while superoxide dismutase, as well as glutathione peroxidase are enzymes involved in its production and degradation. Hence, the activity of these enzymes impacts hydrogen peroxide levels and consequentially the ability of ccRCC cells to evade negative effect of reactive oxygen species.
Keywords: clear cell renal cell carcinoma, redox homeostasis, hypoxia inducible factor, glutathione S-transferases, superoxide dismutase, glutathione peroxidase